Lectotypification of Thalictrum chayuense (Ranunculaceae), with its reduction to the synonymy of T. tsawarungense, both described from Zayu in southeastern Xizang (Tibet), China - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2022)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that the holotype itself and the type collection of Thalictrum chayuense, which was described from Zayu county in southeastern Xizang (Tibet), China, are mixed, consisting of two taxa, T. chayuense and T. nepalense. Lectotypification is proposed for T. chayuense herein. Thalictrum chayuense is then determined to be conspecific with T. tsawarungense, a species described also from Zayu in southeastern Xizang. We therefore reduce T. chayuense to the synonymy of T. tsawarungense.